Beta‐blockers are under‐prescribed in patients with chronic obstructive pulmonary disease and co‐morbid cardiac disease. Issue 11 (November 2016) - Neef, P. A.; McDonald, C. F.; Burrell, L. M.; Irving, L. B.; Johnson, D. F.; Steinfort, D. P.
Abstract : The use of beta‐blockers in patients with chronic obstructive pulmonary disease and co‐morbid cardiovascular disease is controversial, despite increasing evidence to support their use as safe and efficacious. This study retrospectively assessed the rates of beta‐blocker prescription in patients admitted to two Australian tertiary hospitals for acute exacerbation of chronic obstructive pulmonary disease. This revealed that less than half of patients (45%) with known cardiac indications were receiving beta‐blocker therapy, evident across all degrees of airways disease severity. Further work is needed to ensure that medical management of this patient group is optimised.